EVALUASI PROGRAM KERINGANAN PAJAK KENDARAAN BERMOTOR PROVINSI LAMPUNG TAHUN 2023 - Aripah, Widia; Pramazuly, Ayu Nadia; Mosshananza, Hinfa (Jurnal Progress Administrasi Publik, 2025)
This research is motivated by Lampung Governor Regulation Number 6 of 2023 concerning Motor Vehicle Tax Relief and Motor Vehicle Title Transfer Fees which aims to increase PAD from the PKB and BBNKB sectors, synchronize motor vehicle ownership data, update, integrate and synchronize motor vehicle ownership data before the implementation of the provisions of Article 74 of Law Number 22 of 2009 concerning Road Traffic and Transportation and help ease the burden on the community in paying delinquent motor vehicle taxes. This study aims to determine the evaluation of the Lampung Province Motor Vehicle Tax Relief Program Year 2023 and to determine the inhibiting factors in the implementation of the Lampung Province Motor Vehicle Tax Relief Program Year 2023. The method used in the research is qualitative method, data and information from informants obtained through observation, interviews and documentation to the direct research location. The study evaluates the Lampung Province Motor Vehicle Tax Relief Program Year 2023 case study at SAMSAT Mall Chandra Tanjung Karang, with a research focus on Effectiveness, Efficiency, Adequacy, Responsiveness and Accuracy. Based on the results of research conducted at SAMSAT Mall Chandra Tanjung Karang, the Evaluation of the Lampung Province Motor Vehicle Tax Relief Program in 2023 based on the Effectiveness indicator has been effective in helping increase PAD revenue for Lampung Province and easing the burden on the public to pay taxes, while for the Sufficiency indicator there is a decrease in the number of vehicles so that data synchronization becomes less effective. And during the implementation of the Relief Program, there were service constraints, socialization constraints and sanction enforcement constraints.   Keywords: Evaluation; Program; Tax; Vehicle